Dampak Program Pengabdian Masyarakat dalam Meningkatkan Literasi Al-Qur'an di Perumahan The Tamar Village - Saputra, Adha; Ahmad, Raihan Fadhillah; Kusnaldi, Fiky; Paputungan, Dwi Fardha Nabawi; Kurniawan, Fiky (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2025)
Qur'anic literacy is a fundamental aspect of Islamic education that contributes to the understanding and application of Islamic teachings in daily life. Community service programs play a crucial role in enhancing Qur'anic literacy, especially in residential areas with diverse social backgrounds. This study aims to analyze the impact of community service programs on improving Qur'anic literacy in The Tamar Village residential area. The research employs a qualitative approach with a case study method, involving observations, interviews, and program documentation analysis. The findings reveal that community service programs based on Qur'anic learning, such as tahsin, tahfidz, and tafsir study sessions, contribute to the improvement of participants' ability to read and comprehend the Qur'an. Additionally, community involvement in these programs raises awareness of the importance of Qur'anic education for younger generations. In conclusion, community service programs positively impact Qur'anic literacy in residential environments, highlighting the need for further development and sustainability to maximize their benefits.